A 2D-speckle tracking analysis in patients undergoing trastuzumab in non-metastatic breast cancer. (3rd October 2022) - Springhetti, P; Bergamini, C; Niro, L; Ferri, L; Trento, L; Minnucci, I; Tafciu, E; Maffeis, C; Benfari, G; Rossi, A; Fiorio, E; Ribichini, F
Abstract: Background: Trastuzumab (TZ) is widely used for his key role in HER2 positive breast cancer. However, the most concerning cardiovascular complication is cardiotoxicity. Many studies have highlighted the importance of screening for subclinical myocardial dysfunction using left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS). However, there are only few studies investigating a possible atrial damage. Purpose: Aim of this study is to analyze the modification of GLS and peak atrial systolic longitudinal strain (PALS) in patients undergoing therapy with TZ in a follow-up period of 12 months. The eventual fluctuation of left atrial function under chemotherapy was evaluated and the correlation between subclinical atrial disfunction and early left ventricular impairment was investigated. Methods: 105 women affected by breast cancer treated with TZ were enrolled. Each patient underwent a complete echocardiography at baseline and every 3 months. 37 patients (35%) were excluded from the left atrial function analysis while LV function evaluation was performed in 83 patients (21%). Exclusion criteria were poor quality imaging and lack of a complete follow up with consequent missing data. 2D-Speckle tracking analysis was performed at baseline and at each examination using Tomtec software in order to analyze both atrial and left ventricular function. Subclinical LV disfunction was defined as a GLS reduction of ≥15% compared to the baseline value. Left atrial impairment was arbitrary defined as a PALS reduction of ≥25% compared to the initial value. Finally, trends of GLS and PALS during 12 months-follow up periods were analyzed. Additionally, we explored if diabetes and renal impairment were associated with more prevalent atrial subclinical disfunction as demonstrated in previous studies. Results: A total of 49% patients developed subclinical LV dysfunction. Similarly, 48% patients showed a left atrial impairment. Interestingly a significant (p=0.0001) reduction in GLS was observed during the follow-up, particularly in the first six months of treatment. PALS showed a similar trend with a significant decrease during the whole 12 months-follow up (p=0.0001) and mostly in the first 6 months. 6 patients presented a diagnosis of diabetes at baseline, and presented lower PALS compared to the non-diabetic counterpart (37.6±9.9% vs 48.7±12.2%, p=0.03). 2 patients presented a significant renal impairment (eGFR ≤30 ml/min). Similarly, these patients presented a lower PALS at baseline (32±7 and 48±7; p=0.05). Conclusions: In patients treated with Trastuzumab development of left atrial impairment is frequent and PALS modifications follow a similar pattern to GLS variations during the treatment, suggesting a possible cardiotoxic effect of such therapy on both atrial and left ventricular myocardium and physiology. Funding Acknowledgement: Type of funding sources: None.